What is comma doing here?

Calculus Level 5

0 x 3 e 2 x e 3 x d x \large \int _{ 0 }^{ \infty }{ \frac { { x }^{ 3 } }{ { e }^{ 2x }-{ e }^{ 3x } } dx }

If the value of the integral above is equal to

π A B + C D -\dfrac{\pi^A}B + \dfrac CD

where A , B , C A,B,C and D D are positive integers with C , D C,D coprime, find A + B + C + D A+B+C+D .


The answer is 78.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Tanishq Varshney
Jan 15, 2016

0 x 3 e 3 x ( 1 e x ) d x \large{-\displaystyle \int^{\infty}_{0}\frac{x^3}{e^{3x}(1-e^{-x})}dx}

0 x 3 r = 1 e ( r + 2 ) x d x \large{\Rightarrow - \displaystyle \int^{\infty}_{0}x^{3} \displaystyle \sum^{\infty}_{r=1}e^{-(r+2)x} dx}

Put ( r + 2 ) x = t (r+2)x=t

0 t 3 e t d t r = 1 1 ( r + 2 ) 4 \large{\Rightarrow - \displaystyle \int^{\infty}_{0} t^{3}e^{-t} dt \sum^{\infty}_{r=1} \frac{1}{(r+2)^{4}}}

Recall gamma function

Γ ( 4 ) ( r = 1 1 r 4 1 1 2 4 ) \large{\Rightarrow - \Gamma(4) \left( \displaystyle \sum^{\infty}_{r=1} \frac{1}{r^{4}}-1-\frac{1}{2^4} \right)}

= 3 ! ( 17 16 ζ ( 4 ) ) \Large{=3! \left(\frac{17}{16}- \zeta(4) \right)}

51 8 π 4 15 \Large{\boxed{\frac{51}{8}-\frac{\pi^4}{15}}}

Aditya Kumar
Jan 15, 2016

I = 0 x 3 e 2 x e 3 x d x = 0 e 3 x x 3 e x 1 d x I=\int _{ 0 }^{ \infty }{ \frac { { x }^{ 3 } }{ { e }^{ 2x }-{ e }^{ 3x } } dx } \\ \quad =\int _{ 0 }^{ \infty }{ \frac { { { e }^{ -3x }x }^{ 3 } }{ { e }^{ -x }-1 } dx }

Now we substitute: e x = x { e }^{ -x }=x

I = 0 1 x 2 ( l n x ) 3 x 1 = ψ 3 ( 3 ) \therefore \quad I=\int _{ 0 }^{ 1 }{ \frac { { x }^{ 2 }{ \left( lnx \right) }^{ 3 } }{ x-1 } } \\ \quad \quad \quad \quad ={ \psi }_{ 3 }\left( 3 \right)

We use the relation: ψ n ( z ) = ( 1 ) n + 1 n ! ζ ( n + 1 , z ) { \psi }_{ n }\left( z \right) ={ \left( -1 \right) }^{ n+1 }n!\zeta \left( n+1,z \right)

Here ζ ( n + 1 , z ) \zeta \left( n+1,z \right) is Hurwitz Zeta function.

I = 3 ! ζ ( 4 , 3 ) = 3 ! n = 0 1 ( n + 3 ) 4 = π 4 15 + 51 8 \therefore \quad I=-3!\zeta \left( 4,3 \right) \\ \quad \quad \quad =-3!\sum _{ n=0 }^{ \infty }{ \frac { 1 }{ { \left( n+3 \right) }^{ 4 } } } \\ \quad \quad \quad =\frac { {- \pi }^{ 4 } }{ 15 } +\frac { 51 }{ 8 }

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...